Hverdagslivet i vikingetidens Vorbasse: Mellem ældgamle træk og revolutionerende nyt - Hvass, Lone; Hvass, Steen (Kuml, 2025)
Everyday life in Viking Age Vorbasse Between ancient practices and revolutionary innovations Over the past 30 years, hundreds of Iron Age and Viking Age villages have been excavated, but Vorbasse remains unique due to its state of preservation and the proportion of the site that was uncovered in the 1970s and 80s. In the Early Viking Age, the Vorbasse village was small, hardly the size of the average of Jutland village, but it was still the most important settlement in its immediate area (fig. 1). Despite only consisting of six farms, it nevertheless became a church town and the largest local ejerlav (= vill or cadastral district). The village is classified as a typical adelby (= noble town) with extended settlement continuity. Six wells associated with the Early Viking Age village were excavated at Vorbasse, and these were found to contain many well-preserved wooden objects. Since most of these wells have been dated dendrochronologically, the objects found in them can also be dated accurately. Preserved wooden objects are rare finds in the Viking Age villages excavated in Denmark. Conversely, the preservation conditions at early urban sites from the Viking Age and Early Middle Ages are so favourable that many wooden objects associated with activities in daily life have been recovered. The largest body of material is from Hedeby, and the impression gained here is that wooden household objects constituted a significantly larger group than those of pottery, soapstone and other materials combined. The assemblage of wooden artefacts recovered from Vorbasse includes many already known types, such as the wooden bowl with a handle, seen in many variants elsewhere, including at Hedeby and at Trelleborg on Zealand (figs. 12a and 12d). The stave-built bucket (fig. 12 g) is represented at Trelleborg. Similar spades to the Vorbasse examples (fig. 12c) have been found at several other sites, for example the royal mounds at Jelling and the ramparts of Danevirke near Hedeby. Similar ladders to those from Vorbasse are also seen elsewhere, including at the site of Næs in southern Zealand (figs. 8b and 11). Wagon axles, too, are known from other sites, including a well-preserved identical example from Viborg Søndersø. But the trough, baking peel (fig. 12c) and hayfork (fig. 12b) have as yet no parallels at other Viking Age sites in Denmark.